Protptipe Sistem Kontrol Lampu LED Melalui Jaringan Internet Berbasis Arduino - Anenda Happy Safitra (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2021)
As technology has developed rapidly nowadays, it arises some impacts. Controlling electronic devices using the smart home application can ease users to control household electronic equipment to reduce el,ectricity wastefulness when the users forget to turn them off. Towards the aim, the author conducted research on the energy efficiency of lamps used in Internet of Things (IoT) technology.The research developed a controlling system (on-off) of 5 arduino-based LED lamps. The website would control the LED lamps which will send data to the server where the server will continue the data to arduino to read the command: ON or OFF. Next, arduino will send the LED’s status to the server to perform the LED status display on the website. Blackbox testing is used to better utilize the functional aspects of the system designed for users’ convenience in controlling LED lamps based on the appearance of the website. Therefore, the system can show that the functions of both hardware and website controlling the LED lamps are running well and can be used by users easily and usefully.